Instrument to analyse communication in a Community of Inquiry when using emerging methodologies - García Lira, Keidy; Gutiérrez-Santiuste, Elba (Revista Fuentes, 2022)
There is a growing interest in learning in Higher Education using flipped classroom and m-learning. This study constructs an original instrument to obtain information on the levels perceived by the students of the three presences of the Community of Inquiry model with these emerging methodologies. The instrument consists of 21 items, based on the instrument developed by Arbaugh et al. (2008), which were adapted to flipped classroom and m-learning. This instrument was distributed to 121 students from two different universities. Cochran’s Q test was run to verify whether there was agreement between the opinions of five experts. Student t-test results for independent samples indicate similarity in the opinions of the two groups of students. Information analysis techniques, exploratory factor analysis, and reliability tests were also used to validate it. The analysis revealed three factors coinciding with cognitive presence, social presence and teaching presence as proposed by the theoretical model. Cronbach’s Alpha confirmed the reliability of the tool as a whole and its several dimensions. The results indicate that it is a valid and reliable instrument for measuring the levels perceived by the students of the three presences of the Community of Inquiry model when using flipped classroom and m-learning.